Trypanosoma tertium n. sp.: prevalences in natural hosts and development in the mosquito vector - Kulich Fialová, Magdaléna; Kapustová, Anna; Čepička, Ivan; Svobodová, Milena (Parasitology, 2025)
Avian trypanosomes (Trypanosoma, Kinetoplastea) are successful blood parasites occurring worldwide. These parasites are usually non-pathogenic to their avian hosts, thus neglected in studies regarding their life cycles and vectors. Several families of blood-sucking dipteran insects, including mosquitoes, have been identified as vectors of avian trypanosomes. Mosquitoes have been experimentally confirmed as vectors of Trypanosoma culicavium and Trypanosoma thomasbancrofti. In this study, we describe a third species of avian trypanosomes occurring in mosquitoes, designated as Trypanosoma tertium n. sp. This species can be distinguished from related trypanosome species based on morphology and small subunit rRNA gene sequence. Two isolates of T. tertium n. sp. obtained from a mosquito and a bird host were able to infect two subspecies of laboratory Culex pipiens mosquitoes, with infection rates reaching 60% and heavy infections in 90% of positive females. In infected mosquitoes, trypanosomes occurred as long epimastigotes in the midgut and short epimastigotes and rosettes in the hindgut. Putative infectious stages were detected in the diuretic liquid of infected mosquitoes, suggesting, besides transmission through ingestion of the infected vector, a possible transconjunctival infection. Among wild mosquitoes, avian trypanosomes were detected exclusively in Cx. pipiens with 3.3% total prevalence, while T. tertium n. sp. prevalence was only 0.08% among 1128 dissected Cx. pipiens individuals. In birds, T. tertium n. sp. was detected in 8 species within which the prevalence was 1.3% (686 birds), while it was 0.3% in total (3084 birds). We discuss the relationship of the newly described T. tertium n. sp. with other mosquito-transmitted trypanosomes.
Keywords: Trypanosomiasis; vector; Culex; fylogeneze; trypanozomiáza; Phylogeny; Mosquito Vectors; prevalence; komáří přenašeči; avian blood parasite; nemoci ptáků; Animals; ženské pohlaví; transmission; zvířata; Bird Diseases; Prevalence; monoxenous Kinetoplastea; phylogeny; Female; morphology; Trypanosoma